A STUDY ON SPEAKING ABILITY OF THE SECOND YEAR STUDENTS OF SMK LABOR PEKANBARU - Yulia depi; Effendy Gultom; Fakhri Ras (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This descriptive research is aimed at finding out the ability of thesecond year students of SMK Labor Pekanbaru in speaking. Forty-one students ofOffice Administration class in the second semester of academic year 2017/2018 werechosen to become the sample by using cluster random sampling technique. The totalpopulation of the second year students of SMK Labor Pekanbaru is large enough to betaken as sample, it is select the sample by using cluster random sampling technique.The instrument of the research is a speaking test focusing on procedure texts. The datawere analyzed by using five components of speaking. They are: pronunciation,grammar, vocabulary, fluency, and comprehension. The result shows that the meanscore of the speaking test the second year students of SMK Labor Pekanbaru is 60,81.This figure is classified into mediocre level. The highest score of speaking test is 62,60(good level) for pronunciation and the lowest score of speaking test is 57,41 (mediocrelevel) for grammar. Therefore, it can be concluded that the speaking ability of thesecond year students of SMK Labor Pekanbaru is in the range of mediocre level.Key Words: Students’ Speaking Ability, Procedure Texts.